Extended impact of the COVID-19 pandemic: Trajectories of mental health and substance use among U.S. adults, September 2020–August 2021 - Xiangyu Tao; Tingting Liu; Salvatore Giorgi; Celia B. Fisher; Brenda Curtis (Drug and Alcohol Dependence Reports, 2023)
Background: Americans reported significant increases in mental health and substance use problems after the COVID-19 pandemic outbreak. This can be a product of the pandemic disruptions in everyday life, with some populations being more impacted than others. Objectives: To assess the ongoing impact of the COVID-19 pandemic on mental health and substance use in U.S. adults from September 2020 to August 2021. Methods: Participants included 1056 adults (68.5% women) who participated in a national longitudinal online survey assessing the perceived impact of COVID-19 on daily life, stress, depression and anxiety symptoms, and alcohol and cannabis use at 3-time points from September 2020 to August 2021. Results: Individuals with lower self-reported social status reported the highest perceived impact. Participants’ perceived impact of the COVID-19 pandemic on daily life, stress, anxiety, and alcohol use risk significantly decreased over time but remained high. However, there was no change in depressive symptoms and cannabis use. Higher levels of perceived impact of the pandemic significantly predicted both more baseline mental health concerns and lower decreases over time. Lower self-report social status predicted more baseline mental health concerns and smaller decreases in those concerns. Black adults reported significantly higher cannabis use rates than non-Hispanic White adults. Conclusion: The impact of COVID-19 on daily life continued to be a risk factor for mental health during the second wave of the pandemic. In addition to infection prevention, public health policies should focus on pandemic-related social factors such as economic concerns and caretaking that continue to affect mental health.